Development of Interlocking Concrete Blocks with Added Sugarcane Residues - Bruno Ribeiro; Tadaaki Uchiyama; Jun Tomiyama; Takashi Yamamoto; Yosuke Yamashiki (Fibers, 2020)
The use of sugarcane residues in mortar and concrete is believed to contribute to a reduction of costs and environmental problems, such as the reduction of mining of natural aggregates and incorrect disposal of the sugarcane residues. Bagasse fiber has a high water retention rate and thus may be considered as a countermeasure for urban heat islands. Because of these properties, bagasse fiber and bagasse sand were added into the preparation of the interlocking concrete blocks. An investigation of the flexural strength and the contribution of the sugarcane residues against an urban heat island was made. The results showed that, by adding 2.0% of bagasse fiber and 5.0% of bagasse sand in concrete, the flexural strength and the water retention content increased in comparison to the control composite. Moreover, the surface temperature and the water evaporation rate of the blocks were smaller in comparison to the control composite.